THE IMPLEMENTATION OF OUT DOOR STUDY LEARNING MODEL FOR GEOGRAPHY AT XI IPS CLASS OF SMAN 6 SIGI - Huljana, Sara; Nurvita, Nurvita (Tadulako Social Science and Humaniora Journal, 2020)
This study aims to describe the implementation of outdoor study learning model and student’s perceptions onoutdoor study learning model. The study applied descriptive qualitative method. The number of populationwas 50 students and the sample of the study was 27 students. Techniques of data collection were observation, questionnaire, and documentation. The result of applying outdoor study learning model towards students’observation was 86.6% which included in the very good category. Moreover, the result of teacher’ activity was 77.7% included in thevery well implemented category. Based on the lesson plan and the average result of the students’ questionnaire, the results obtained were 49.37%for the category of strongly agree, 26.67% for the category agree, 20.48% for the category of disagree, and 3.48% for the category of strongly disagree. It couldbe concluded that the results of students’ perception on outdoor study learning model was 49.37% which included in good category.